Implementation of the Multi-Objective Optimization Method based on Ratio Analysis (MOORA) in the Decision Support System for Determining the Beneficiary of BPJS Health Contribution Assistance (Case Study: Loru Village, Sigi Regency) - Hajra Rasmita Ngemba; Rudy Reynold Richardo; Rosmala Nur; Muhammad Rusydi; Christian Lopo; Mayin Nu; Annisa Putri Febrina (LPPM Universitas Tadulako, 2021)
Introduction: This study aims to build an application that can carry out the selection process for prospective recipients of contribution assistance so that it is easier and becomes an alternative choice for the Village Government in determining eligible residents for BPJS Health contribution assistance in Loru Village, Sigi Regency. Methods: This decision support system application is web-based using the Hypertext Prepocessor (PHP) programming language with the Multi Objective Optimization method On The Basis Of The Ratio Analysis (MOORA), using sublime text 3 software and also MySQL as the database. In this study, 444 households were used as data for heads of households. With the system, orders will be carried out objectively and in detail. To determine which residents are truly entitled to receive assistance, this is done by compiling citizen data by considering the value of the MOORA method formula for each of the specified criteria. Result: The results that have been carried out by this author are a solution to determine the recipients of BPJS Health contribution assistance in Loru Village, Sigi Regency, so that the selection process can be more effective in terms of time and operation. Conclutions: Based on manual calculations as a comparison with the calculation of the system built, the same results were obtained. This shows that the system built can process the selection of potential recipients of contribution assistance. The result of the system process using the MOORA method is the ranking of PBI candidates with the highest rank to the lowest rank.